PERAN KEMENTRIAN SOSIAL RI SENTRA ABISEKA PEKANBARU DALAM ADVOKASI KORBAN KASUS TINDAK PIDANA PERGAGANGAN ORANG - Tengku, Ariya; Rio Tutrianto, (Sisi Lain Realita, 2023)
Trafficking in Persons is one of the crimes against humanity that is very worrying and requires serious attention from various parties. Victims of Trafficking in Persons often experience physical and psychological suffering and exploitation that can cause prolonged traumatic effects. Therefore, comprehensive advocacy efforts are needed to restore the condition of victims and protect and uphold their rights. This research aims to analyze the role of the Indonesian Ministry of Social Affairs Sentra Abiseka Pekanbaru in advocating for victims of Human Trafficking Crime cases. A qualitative approach with in-depth interview, observation, and document study methods was used in this research. Data was obtained through interviews with the head of the Abiseka Center, social workers, social counselors, nurses, and victims of Trafficking Crimes who have received assistance at the Abiseka Center Pekanbaru. The results showed that the Abiseka Center has an important role in advocating for victims of Human Trafficking through various programs and services, such as social rehabilitation, vocational training, medical, psychological, and legal assistance, as well as preventive and promotive efforts to the community. In carrying out its role, Sentra Abiseka faces supporting factors such as victim protection policies, cooperation with various parties, and systematic programs, as well as inhibiting factors such as limited human resources, community stigma, victim trauma, and diverse victim characteristics. To face these challenges, Sentra Abiseka implements strategies such as building trust with victims, a comprehensive approach, comprehensive assistance, cooperation with other centers, and optimizing the role of social workers and social counselors. The analysis was conducted using criminal policy theory and victim typology theory to understand the efforts to overcome the crime of Human Trafficking and to design programs that are in accordance with the characteristics and specific needs of victims.